Shared genetic factors and the interactions with fresh fruit intake contributes to four types squamous cell carcinomas. - Mengqing Mo; Can Hou; Huangbo Yuan; Renjia Zhao; Mingyang Chen; Yanfeng Jiang; Kelin Xu; Tiejun Zhang; Xingdong Chen; Chen Suo (PLoS ONE)
Studies have reported risk factors for a single-squamous cell carcinoma(Single-SCCs). However, the shared common germline genetic factors and environmental factors have not been well elucidated with respect to augmented risk of pan-squamous cell carcinoma(Pan-SCCs). By integrating a large-scale genotype data of 1,928 Pan-SCCs cases and 7,712 age- and sex-matched controls in the UK Biobank cohort, as well as multiple transcriptome and protein databases, we conducted a multi-omics analysis. Genome-wide association analysis (GWAS) was used to identify genetic susceptibility loci of SCCs. High resolution human leucocyte antigen (HLA) alleles and corresponding amino acid sequences were imputed using SNP2HLA and tested for association with SCCs. Credible risk variants (CRVs) were combined risk SNPs reported in GWAS Catalog and our study, followed by comprehensive bioinformatics analyses. We identified six novel index SNPs in the progression of SCCs, which were also strongly interacted with fresh fruit intake. Moreover, our study systematically characterize the HLA variants and their relationship to SCCs susceptibility. We identified HLA-A*01 and six HLA-A amino acid position were associated independently with SCCs. Credible risk variants were annotated to 469 target genes, further GO and KEGG Pathway Enrichment Analysis showed that SCCs genes were primarily involved in immune-related pathways, espechially regulated by HLA region. The transcriptome analysis showed that there were 270 differentially expressed genes(DEGs), with the upregulated genes were enriched in the regulation of stem cell differentiation, proliferation, development, and maintenance. The PPI Network and Modular Analysis uncovered the Keratin(KRT) genes may serve as a potential marker in SCCs. Our results illustrate the molecular basis of both well-studied and new susceptibility loci of SCCs, providing not only novel insights into the genetic commonality among SCCs but also a set of plausible gene targets for post-GWAS functional experiments.